THE INFLUENCE OF LEARNING MOTIVATION ON THE LEARNING OUTCOMES OF CLASS XII STUDENTS IN ACCOUNTING SUBJECTS PUBLIC HIGH SCHOOL 1 SELAYAR - muttaqinah, Andi Ratu; Hasyim, Sitti Hajerah; Tikollah, M. Ridwan; Azis, Muhammad; Dunakhir, Samirah (JURNAL EDUSCIENCE, 2023)
The purpose of this study is to analyze the influence of learning motivation on the learning outcomes of students in gradesXII IPS 1 and XII IPS 2 of SMA Negeri 1 Selayar. A total of 39 students from classes XII IPS 1 and XII IPS 2 of SMA Negeri 1 Selayar were used as the research samples. Instrument tests and hypothesis tests were used as data analysis techniques using SPSS 22. Valisidad tests and reliability tests are part of the instrument test. The t-test of the coefficient of determination, the Pearson product-moment correlation analysis and the simple linear regression analysis are hypothesis tests. Based on the research results, the model of simple linear regression equation Y' = 79.136 + 0.128X shows that the competency value of the skills of the problem-based learning model increases by one for every 0.128 units increase in student score in the class. Motivation to learn has a significant effect on student learning outcomes based on the results of the t-test, which was 0.004 < 0.005. The coefficient of determination analysis yielded an r2 value of 19.4%, indicating that learning motivation contributes 19.4 to student learning outcomes. The results of the product-moment correlation analysis showed a weak correlation between learning motivation and students' learning outcomes, with a Pearson correlation value of 0.213.Keywords: learning motivation; learning outcomesAbstrak Tujuan penelitian ini adalah untuk menganalisis bagaimana pengaruh motivasi belajar terhadap hasil belajar siswa kelas XII IPS 1 dan XII IPS 2 SMA Negeri 1 Selayar. Sebanyak 39 siswa kelas XII IPS 1 dan XII IPS 2 SMA Negeri 1 Selayar yang dijadikan sebagai sampel penelitian. Menggunakan SPSS 22, uji instrumen dan uji hipotesis merupakan teknik analisis data yang digunakan. Uji valisitad dan uji reliabilitas merupakan bagian dari uji instrumen. Uji-t koefisien determinasi, analisis korelasi pearson product moment, dan analisis regresi linear sederhana merupakan uji hipotesis. Berdasarkan temuan penelitian, model persamaan regresi linear sederhana Y’ = 79,136 + 0,128X menunjukkan bahwa nilai kompetensi keterampilan model pembelajaran berbasis masalah meningkat satu untuk setiap nilai tambah siswa di kelas meningkat sebesar 0,128 satuan. Motivasi belajar berpengaruh signifikan terhadap hasil belajar siswa, berdasarkan hasil uji-t diperoleh 0,004 < 0,005. Analisis koefisien determinasi menghasilkan nilai r2 sebesar 19,4% yang menunjukkan bahwa motivasi belajar memberikan kontribusi sebesar 19,4 terhadap hasil belajar siswa. Hasil analisis korelasi product moment menunjukkan adanya korelasi yang lemah antara motivasi belajar dengan hasil belajar siswa, dengan nilai korelasi pearson sebesar 0,213.Kata Kunci: motivasi belajar; hasil belajar